Forests for the future - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Forests for the Future. Local Strategies for Forest Protection, Economic Welfare and Social Justice. Edited by P Wolvekamp. Zed Books in association with Both ENDS and Econet, 1999. 288 pp. ISBN 1 85649 757 7. US$25 26 (excluding postage) Zed B